ANTARA DUKUNGAN SOSIAL KELUARGA DAN SELF EFFICACY DENGAN KEMANDIRIAN BELAJAR PADA SISWA SMKN 2 MEDAN - Perita Wati S; Cut Mutia (Universitas Medan Area, 2010)
This study aims to determine Is there a relationship Social Support and Self Efficacy with Students In SMKN2 Medan. In proving the above hypothesis, we used data analysis method Multiple Regression. Based on data analysis of the results obtained: 1). that there is a significant negative relationship between family social support and self-efficacy for learning on students' self-reliance which can in coefficients (F reg = 4.771 with p> 0.05) where F reg (F calculated)> F table (4.771> 3.159). 2). Based on the results of data analysis according to the formula of partial correlation analysis of the first level of known results as follows it can be concluded that the contribution of family social support variables and self-efficacy is 14% while the rest 86% influenced by other factors not discussed or examined by the researcher such as intelligence, parenting, community life pattern of the system. In general, the results of this study illustrate that there is a relationship between social support and self-efficacy in students with learning independence.